Analysis of the Characteristics and Strategies of Two Types of Painting Bloggers on the Internet - Wang, Yicheng (International Journal of Social Sciences and Public Administration, 2024)
In the realm of the Internet, art painting bloggers remain sparse, yet pivotal. This paper delves into the domain, focusing on the evolution of Internet self-media from textual to video platforms and the emerging prominence of art painting bloggers. Notably, painting facilitates visually intense content creation, offering a competitive edge over text-based mediums. However, amidst escalating competition, stylistic variations significantly influence account value, demanding a delicate balance between creativity and quality. Through iterative experimentation and data analysis, optimal competitive advantages can be harnessed. The study concludes by emphasizing the importance of strategic adaptation within this dynamic landscape. This work sheds light on the nuanced characteristics and effective strategies employed by two distinct types of painting bloggers, offering valuable insights for practitioners in the field.